Gamificación para el aprendizaje de biología en estudiantes de bachillerato general unificado de la Unidad Educativa “Huambaló”. - Darío Roberto, Miranda Vera (2021)
Gamification is an active methodology that encourages teacher creativity to generate dynamic and interactive learning in the student; a gamified system has three essential components: Mechanics, Dynamics, and Aesthetics. This research is called: "Gamification for the learning of Biology in students of the Unified General Baccalaureate of the Unidad Educativa "Huambaló," where the research is based on pedagogical currents such as Brunner's Constructivism, it proposes that learning must not be "thought," also, there must be "exploration and interaction"; Siemens' Connectivism indicates that the transmission of knowledge is done through nodes or connection networks using non-human devices, from the biological point of view the playful process, from the evolutionary point of view is considered as: "The preparation of the child for life," furthermore, student motivation plays a vital role in the abstraction of knowledge; the motivating factor is related to the intercultural relationships present in the classroom, whether they are virtual or face-to-face. The study is based on a mixed approach, where for the qualitative research, the information was obtained through interviews with the teachers. For the quantitative approach, surveys were applied. It also has a descriptive-explanatory, field, documentary, non-experimental nature. For data collection, an MS Teams tool was used with the interviews; Google Forms for the surveys. Once the data was processed and the truthful information was obtained, a virtual classroom is proposed that relates gamification with the learning of Biology, called "Kuriñam" (Golden Road), applied on an LMS Moodle platform supported by various platforms for gamification that is available to the students. It is supported by technology and interculturality.